EVALUATION OF MICROFLORA IN PETROL CONTAMINATED SOIL - K. A. VIJAYALAKSHMI; SUDHA RAO; A. B. VEDAMURTHY (The Bioscan, 2010)
The present paper intends to know the infertility of soil caused by hydrocarbon contamination. To understand this, soil sample was taken in three different pots and was polluted with 0 mL, 50 mL, and 100 mL of petrol. The pot with 0 mL petrol served as control. Quantitative analysis like checking the bacterial counts and qualitative analysis, like biochemical tests was done on day 10 and day 20 after incubation with the fuel. The bacterial count decreased initially during the incubation period but gradually increased as the incubation period progressed to day 20. The bacterial population in control sample was positive for nitrogen fixation test and did not show any positive result for phosphate solubilization. The bacterial population in petrol treated soil samples was negative for both nitrogen fixation test and phosphate solubilization test which showed that those microorganisms which were present in fertile soil were absent here. The samples which were incubated for longer period of time, though gave negative results for biochemical analysis, showed majority of grampositive cocci population, which are known to be one of the potential degraders of hydrocarbon (Toledo et al., 2006).